Analisis Kritis Implementasi Pendidikan Inklusi dalam Perspektif Teori Keadilan Sosial: Kajian Literatur Terkini - Riski Amalia; Nurfadillah; Mutia Marsya; Laeli Qadrianti; Wahyuningsih; Irwin Hidayat (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
This study is motivated by the suboptimal implementation of inclusive education in realizing substantive educational justice, despite being normatively strengthened through policies and academic discourse since 2022. The gap between ideal concepts and actual practices is still influenced by structural, pedagogical, and cultural barriers. This study aims to analyze the implementation of inclusive education from the perspective of social justice theory and to examine the extent to which such practices reflect the principles of justice in the dimensions of distribution, recognition, and participation. The study employs a qualitative approach through a systematic literature review method enriched with critical analysis of scientific articles published between 2022 and 2026, using thematic and comparative analysis techniques. The findings indicate that inclusive education is not merely related to expanding access for students with special needs, but also requires a reconstruction of the educational paradigm toward substantive justice that positions identity recognition, active participation, and resource distribution as interconnected dimensions. The synthesis of this study reveals that the success of inclusive education is more strongly determined by the transformation of school culture and the integration of diversity-responsive policies rather than merely fulfilling the administrative requirements of inclusion policies. Therefore, inclusive education has the potential to serve as an instrument of social justice if it is directed toward systemic transformation oriented to equality in learning experiences and the empowerment of all learners.